Manajemen Pemasaran Sekolah Menengah Kejuruan Islamic Center Cirebon Dalam Membangun Brand Image Untuk Meningkatkan Minat Calon Peserta Didik - Asep - Kurniawan (Holistik, 2022)
Educational Institution manages education marketing properly in order to attract consumer interest. The aim of this research was to determine education marketing management in building a brand image to increase the interest of prospective students in Vocational Schools Islamic Center Cirebon. The method used in this research was descriptive qualitative method. Data collection techniques were in-depth interviews, in-depth observations and documentation studies. The data analysis techniques were data collection, data reduction, data presentation and data conclusions. It shown that the school implemented a process of planning, implementing, and supervising the school's marketing. In addition, schools also implemented supporting factors and minimized obstacles in building a brand image so that it could attract students' interest.